Breakfast Intake and Factors Associated with Adherence to the Mediterranean Diet among Lebanese High School Adolescents - Rana Mounayar; Rana Jreij; Jennifer Hachem; Frida Abboud; Maya Tueni (Journal of Nutrition and Metabolism)
The Mediterranean diet has shown to have positive health impacts on metabolic diseases and cognitive performance. However, Mediterranean countries have witnessed a decreased adherence during the past years and the adoption of a more westernized dietary pattern. The aim of this study was to evaluate the association of Mediterranean diet adherence with sociodemographic, lifestyle, and anthropometric factors among Lebanese high school adolescents. Specifically, we aimed to analyse in this group the association between low adherence and breakfast intake. A cross-sectional survey was carried out on randomly selected students (268 boys and 332 girls), aged between 15 and 18 years old, from private and public schools in Beirut and Mount Lebanon. Data were obtained from self-administered questionnaires and anthropometric measurements. The Mediterranean Diet Quality Index for children and adolescents was used to assess the adherence to the Mediterranean diet. The results showed a high percentage of adolescents having a low adherence (43%), with girls (64.2%) having a significant (p<0.001) higher adherence than boys (35.8%). Furthermore, the study proved that a lower adherence to the Mediterranean diet was significantly associated with a higher risk of obesity (15.5%), breakfast skipping (69.4%), and an unhealthy breakfast options (17.4%). Younger adolescents (47.4%), students from public schools (92.6%), and students with the highest grades (25.3%) had a significantly higher adherence to the Mediterranean diet than those from private schools (7.4%) and older adolescents (18.9%). In conclusion, results should plead for an increased awareness in Lebanese schools, supporting students to be more adherent to the Mediterranean diet, in order to prevent a further increase in metabolic diseases later in adulthood.